2009
DOI: 10.1371/journal.pone.0006408
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling of Central Nervous System Regions in Three Species of Honey Bee during Dance Communication Behavior

Abstract: BackgroundWe conducted a large-scale transcriptomic profiling of selected regions of the central nervous system (CNS) across three species of honey bees, in foragers that were performing dance behavior to communicate to their nestmates the location, direction and profitability of an attractive floral resource. We used microarrays to measure gene expression in bees from Apis mellifera, dorsata and florea, species that share major traits unique to the genus and also show striking differences in biology and dance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 70 publications
7
37
0
1
Order By: Relevance
“…A total of 29 annotated genes and 23 unannotated transcripts (out of 9478 transcripts that passed quality control analysis on the microarray) were differentially regulated ( anova , FDR < 0.05 ) between S → L and S → S bees, either in the OL, MB or both (Table 1). By contrast, 1817 transcripts were differentially regulated between the two brain regions at the same FDR, comparable to a previous study of brain region differences in a different set of foraging bees (Sen Sarma et al 2009).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…A total of 29 annotated genes and 23 unannotated transcripts (out of 9478 transcripts that passed quality control analysis on the microarray) were differentially regulated ( anova , FDR < 0.05 ) between S → L and S → S bees, either in the OL, MB or both (Table 1). By contrast, 1817 transcripts were differentially regulated between the two brain regions at the same FDR, comparable to a previous study of brain region differences in a different set of foraging bees (Sen Sarma et al 2009).…”
Section: Resultssupporting
confidence: 84%
“…Threshold for selection was >60% ‘correct’ dances for either short or long distances (Srinivasan et al 2000) (Table S1). Dissection of frozen brain regions and messenger RNA (mRNA) preparation and amplification were as in the study of Sen Sarma et al (2009).…”
Section: Methodsmentioning
confidence: 99%
“…The use of high‐throughput technologies that make possible measuring the expression of many genes simultaneously, shows that social stimuli induce massive changes ( i.e . hundreds to thousands of differentially expressed genes) in gene expression in the CNS (Whitfield et al , 2003; Kroes et al , 2006; Cummings et al , 2008; Dong et al , 2009; Sen Sarma et al , 2009; Wurm et al , 2010). This approach has made it clear that social information has broad effects on gene expression and is not restricted to specific genes, and is unravelling how gene regulation underlies social diversity at different levels ( e.g.…”
Section: Genomic Landscapes For Social Plasticity: Immediate Early Gementioning
confidence: 99%
“…Differential socially driven changes in transcriptome profile across different brain regions have also been reported and add an extra level of complexity and opportunities for research ( e.g . songbirds; Lovell et al , 2008: bee dance; Sen Sarma et al , 2009). All these studies have identified complex network of genes whose expression changes in response to socially relevant information.…”
Section: Genomic Landscapes For Social Plasticity: Immediate Early Gementioning
confidence: 99%
“…Candidate genes associated with dominance and aggression in primitively social species can be identified and the activity of these genes can be compared between signallers and recipients within an advanced social species, as well as among species showing different levels of social complexity. Such comparisons can elucidate the possible role of aggression in the performance of a particular communication signal, as well as reveal possible scenarios for signal evolution (Alaux, Sinha, et al, 2009;Sen Sarma, Rodriques-Zas, Hong, Zhong, & Robinson, 2009;Toth et al, 2014.…”
mentioning
confidence: 99%